A Study of Psi-Function - Kumar, Y. Pragathi; Satyanarayana, B. (Journal of Informatics and Mathematical Sciences, 2020)
The aim of this paper is to introduce a new generalization of the well-known, interesting and useful Fox \(H\)-function and \(I\)-function into generalized function, namely, the Psi-function. From which authors obtained I-function defined by Saxena [17] and Rathie [8]. Convergent conditions, elementary properties, and special cases have also been given.